Collaboration and Communication between Hobby Metal Detectorists and Archaeologists in Norway. Issue 3 (August 2022) - Axelsen, Irmelin
Abstract: In this article, the ways in which hobby metal detectorists searching for protected objects in the ploughsoil and archaeologists in Norway have collaborated and communicated throughout the public history of metal detecting in the country is outlined and problematized. Due to the opinions of individual archaeologists working in key positions and the autonomy of the country's local and regional management institutions, there are huge variations in both attitudes and practices toward metal detecting and its practitioners. In some areas, metal detectorists are allowed to search more or less freely, whereas in others, entire fields are protected after a few finds, making continued detecting without formal approval from the authorities illegal. Because of this, and the extreme difference in the activity level of individual detectorists, the number of recorded detecting finds varies immensely across county and regional borders. I suggest that channels for collaboration and communication be formalized and that a national and therefore uniform public reporting system be realized—given that it is, for the time being, largely up to individual archaeologists whether some of the country's most active citizen scientists are equally treated by the archaeological heritage management system in Norway.